Optical Coherence Tomography Angiography of Nonarteritic Cilioretinal Artery Occlusion Alone. (27th January 2021) - Ikebukuro, Toyo; Igarashi, Tsutomu; Kameya, Shuhei; Arima, Takeshi; Kunishige, Tomoyuki; Takahashi, Hiroshi
Abstract : Cilioretinal artery occlusion (CLRAO) is a rare disease. Here, we report the case of a 70-year-old man with nonarteritic cilioretinal artery occlusion alone. The patient was allergic to fluorescein. Therefore, we followed the retinal circulation with optical coherence tomography angiography (OCTA). OCTA at 40 days postonset showed partial improvement in the retinal circulation.